Pre-Screening Counseling in Cervical Cancer Prevention: Implication for Nursing (2011)
Cervical cancer is the second most common cancer among women worldwide, with an estimated 529,409 new cases and 274,883 deaths in 2008, about 86% of the cases occur in developing countries, representing 13% of female cancers (IARC, GLOBOCAN, 2008). All sexually active women are at risk for the development of this disease and it is one of the leading causes of death for middle-aged women in the developing world. It is almost completely preventable, if precancerous lesions are identified and treated early (Carr and Sellors, 2004; Ayinde and Omigbodun, 2003). Uptake of screening services has remained low. Pre-screening counseling (PSC) could help increase compliance with screening schedule. Various studies identified ignorance/lack of knowledge, inappropriate/cultural beliefs about the illness; apprehension, etc., as barriers to utilization of screening services (Gharoro and Ikeanyi, 2006; Mutyaba et al., 2007). Also, a positive correlation between Pap test awareness and utilization was reported by Gharoro and Ikeanyi (2006). Pre-screening counseling is very important in order to achieve the purpose of screening. counseling is a two-way dialogue that enables a woman gain knowledge and improve her ability to make informed choice about type of screening procedure she will undertake, being fully aware of the risks and benefits of such. This was explained using the theory of planned behaviour. The nurse/midwife should be well versed in cervical cancer natural history, prevention and management in order to counsel effectively. She should also avail herself of every opportunity to counsel and inform women about cervical cancer.